Improved thermoelectric performance of Te-doped and CNT dispersed CoSb3 skutterudite bulk materials via HTHP. Issue 75 (19th August 2015) - Sun, Hairui; Jia, Xiaopeng; Lv, Pin; Deng, Le; Guo, Xin; Zhang, Yuewen; Sun, Bing; Liu, Binwu; Ma, Hongan
<x xml:space="preserve">Abstract</x> CNTs were dispersed in Co4Sb11.5Te0.5 skutterudite bulk materials via a HTHP method. The effects of the Te and CNT content on the structure and thermoelectric properties were investigated under different pressures.